“Introduction to Metaphysics” A Critical Analysis to the Persian Translation - Mohammad Javad Safian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This essay will critically examine a translation of Martin Heidegger’s “Introduction to Metaphysics”, in the hope of enriching the art of translation in the field of western philosophy. The method, or in better words, the approach to the essay, is concerned with the prevailing spirit of metaphysics in translation and through an in-depth comparative lens. The translation of “Introduction to Metaphysics” has successfully walked through the reader to the World of the text; nevertheless, the translation of a couple of terms and equivalents have fallen flat. This essay presents a summary of the book, followed by a study of the mentioned terms and equivalents, typos, and grammatical errors. The translation is all in all comprehensible, eloquent and coherent, suggesting the knowledge and efforts he has put into his translating.